Secondary malignant neoplasms after bone and soft tissue sarcomas in children, adolescents, and young adults. Issue 9 (23rd February 2022) - Kube, Stefanie J.; Blattmann, Claudia; Bielack, Stefan S.; Kager, Leo; Kaatsch, Peter; Kühne, Thomas; Sorg, Benjamin; Kevric, Matthias; Jabar, Susanne; Hallmen, Erika; Sparber‐Sauer, Monika; Klingebiel, Thomas; et al.
Abstract : Background: Increased survival in young sarcoma patients comes along with a higher incidence of second malignant neoplasms (SMNs). The incidence, latency, histiotype, and outcome of these patients were analyzed because this information is essential to design evidence‐based long‐term follow‐up care programs for young sarcoma survivors. Methods: Patients entered on clinical trials or registered in registries with a primary sarcoma in 1 of the cooperative sarcoma study groups in the framework of the Society for Pediatric Oncology and Hematology (GPOH) were screened for SMNs. Descriptive analysis, the Kaplan‐Meier method, the Gray model, the Fine‐Gray model, and the Cox regression model were used for the statistical analyses. Results: A total of 159 out of 7079 (2.2%) patients were registered with a SMN. Among them, 104 solid SMNs (65%) and 56 hematologic SMNs (35%) occurred. Median latency from first diagnosis of sarcoma to the diagnosis of SMN was 6.8 years (range, 0‐26.7 years). Cumulative incidence of SMN was 8.8% after 30 years. Five‐year‐survival was 67.1% (95% confidence interval [CI], 66.0‐68.2) for the 7079 patients and it was 45.1% (95% CI, 36.2‐53.6) after the diagnosis of a SMN (subcohort of n = 159 patients). Conclusions: There is a remarkable high cumulative incidence of SMNs after bone and soft tissue sarcomas in children, adolescents, and young adults. Therefore, effective transition as well as risk adapted long‐term follow‐up care programs should be developed and offered to young sarcoma survivors. Lay Summary: Bone sarcomas and soft tissue tumors are rare tumors in children, adolescents, and young adults. The treatment varies, but may comprise chemotherapy, surgery, and/or radiotherapy. Developing a subsequent malignant tumor is a long‐term risk for the patients. To better characterize this risk, we analyzed the data of 7079 patients (up to 21 years old) with bone sarcomas or soft tissue tumors. Our findings provide a basis to counsel young sarcoma survivors on their individual risk of subsequent malignant tumors. Moreover, these data can help to establish recommendations for aftercare in young sarcoma survivors. Abstract : There is remarkably high cumulative incidence of second malignant neoplasms after successful sarcoma therapy in children, adolescents, and young adults. Therefore, effective structured transition as well as risk‐adapted long‐term follow‐up care programs should be developed and offered to young sarcoma survivors.